Injection laryngoplasty as adjunct treatment method for muscle tension dysphonia: Preliminary findings. (30th July 2019) - Novakovic, Daniel; Nguyen, Duong Duy; Chacon, Antonia; Madill, Catherine
Abstract : Objectives: This study examined the effectiveness of injection laryngoplasty (IL) in muscle tension dysphonia (MTD) patients who did not fully respond to voice therapy. It was hypothesized that IL would improve voice quality and voice‐related quality of life measures in MTD. Methods: A retrospective review was conducted on 37 patients with a primary diagnosis of MTD who underwent IL following a suboptimal response to voice therapy (mean age = 43.0 years; standard deviation [SD] = 13.4; range = 23 to 71). Outcome measures included laryngoscopic signs of supraglottic constriction, Voice Handicap Index‐10 (VHI‐10) scores, maximal phonation time, vowel fundamental frequency (F0), standard deviation of F0 (F0SD), harmonics‐to‐noise ratio (HNR), and smoothed cepstral peak prominence. These were compared between baseline and within 3 months following the IL procedure. Results: There was significant decrease in supraglottic constriction. Mean (SD) of VHI‐10 scores decreased from 25.4 (5.7) at baseline to 15.3 (9.3) following IL. This improvement in VHI‐10 was observed in patients with and without baseline glottal insufficiency (GI). Mean (SD) of HNR (decibels) increased from 21.1 (5.4) at baseline to 22.8 (4.3) after IL. Only patients with GI demonstrated a significant improvement in HNR from baseline to post‐IL. No statistically significant differences in other acoustic measures were observed. Conclusions: IL resulted in positive changes in voice‐related quality of life in MTD patients with and without GI. Acoustically, only those with GI demonstrated an increase in HNR following IL. Further studies are needed to examine the effects of IL in MTD. Level of Evidence: 4 Laryngoscope, 130:980–985, 2020